Façonner un lieu dans la ville et une singularité de la marque urbaine : exemple des usages des images photographiques dans le quartier de la Mouraria à Lisbonne - Jacques Galhardo (Confins)
Photography plays an important role in the rehabilitation of old urban centers: it offers the opportunity for local actors to claim, promote or denounce public heritage action. The analysis of photographs, over time, allowed me to understand what is defined as tangible or intangible heritage; But above all the processes of "disocultation" from a blind spot in the city. Far from being merely a communication tool or arrangement, photographic production and its various uses favor the processes of urban integration of a neighborhood, long regarded as marginal by the local actors of Lisbon: the Mouraria. This leads me to discuss the effects of these uses of the image on the neighborhood itself and its inhabitants. This article aims to show, through photographic examples, that the asserted views - far from constructing a convergent image of a neighborhood or the city - produce a set of socio-spatial fragmentations and ambiguities in the construction of the urban, as in the place of the residents. The distinctions between public and private image or between institutional and associative image tend to be less evident as municipal intervention takes place. The photographs can then appear as a material conducive to the manipulation of local actors. I will try to show that the latter also profit from the game by negotiating, in the public space, these images.